Well-defined sensing property of ZnO:Al relative humidity sensor with selected buffer layer. (August 2015) - Yang, Chih Chin; Shen, Jiun Ying
Abstract: The effect of the buffer layer in ZnO:Al sensing film and in ZnO:Al biological sensor with nanometer grain is explored herein. The performance of buffer layer in a ZnO:Al sensor is remarkable. The sensitivity of the ZnO:Al RH sensor with a buffer layer is about 1.1. The rise time of the adsorption reaction from 30% RH to 90% RH for the ZnO:Al RH sensor with buffer layer is about 105 s. Also, the drop time of the desorption reaction from 90% RH to 30% RH is about 19 s. In this research, the sensing performance of the ZnO:Al RH sensor with the selected buffer layer is better than that without the selected buffer layer for the sensing response. Highlights: The n-type and high conductivity ZnO:Al sensing film is successfully completed. The performance of selected buffer layer in ZnO:Al RH sensor is also verified. ZnO:Al RH sensor with selected buffer layer is successfully fabricated. ZnO:Al RH sensor of high sensitivity is revealed. ZnO:Al RH sensor with rapid response is revealed better than commercial product.